2018
DOI: 10.3390/medsci6030061
|View full text |Cite
|
Sign up to set email alerts
|

Contribution of Inhibitor of Differentiation and Estrogenic Endocrine Disruptors to Neurocognitive Disorders

Abstract: The devastating growth in the worldwide frequency of neurocognitive disorders and its allied difficulties, such as decline in memory, spatial competency, and ability to focus, poses a significant psychological public health problem. Inhibitor of differentiation (ID) proteins are members of a family of helix-loop-helix (HLH) transcription factors. ID proteins have been demonstrated to be involved in neurodevelopmental and depressive diseases and, thus, may influence neurocognitive deficiencies due to environmen… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
8
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
3
3

Relationship

2
4

Authors

Journals

citations
Cited by 6 publications
(8 citation statements)
references
References 71 publications
0
8
0
Order By: Relevance
“…According to the diverse genetic pattern obtained from whole-genome methylation sequencing between WT and dnmt3aa KO fish, neurod6b, ptfa1, mafba, isl2a, uncx4.1, dmbx1b, and mab21l2 were associated with neural development, which indicated that dnmt3aa KO affects neurons through these genes. Neurod6, an abbreviation of neurogenetic differentiation 6, was reported to associate with the neurodevelopmental disease, long-term potentiation, as well as synaptic transmission defects [105,106]. In addition, ptfa1 was also considered as one of the regulators of transcriptional homeodomain during neuronal specification [107].…”
Section: The Differences In Neurotransmitters and Methylation Level Of Dnmt3a Gene-deficient Zebrafishmentioning
confidence: 99%
“…According to the diverse genetic pattern obtained from whole-genome methylation sequencing between WT and dnmt3aa KO fish, neurod6b, ptfa1, mafba, isl2a, uncx4.1, dmbx1b, and mab21l2 were associated with neural development, which indicated that dnmt3aa KO affects neurons through these genes. Neurod6, an abbreviation of neurogenetic differentiation 6, was reported to associate with the neurodevelopmental disease, long-term potentiation, as well as synaptic transmission defects [105,106]. In addition, ptfa1 was also considered as one of the regulators of transcriptional homeodomain during neuronal specification [107].…”
Section: The Differences In Neurotransmitters and Methylation Level Of Dnmt3a Gene-deficient Zebrafishmentioning
confidence: 99%
“…Animal studies investigated the effect of known or potential EDCs on neural development via direct or indirect effect on aromatase, estrogen receptors and androgen receptors [17,[46][47][48][49]. Population studies concluded that similar effects exist in human, specifically linking thyroid disruptors during fetal development with cognitive and behavioral impairment [22,[50][51][52][53][54][55] even at low doses.…”
Section: Endocrine Disruptors and Human Healthmentioning
confidence: 99%
“…Nonetheless, while animal studies showed a clear activity of bisphenol A and its correlation with adverse effects on female fertility and pregnancy outcomes [22,48], human study results are still conflicting. Some studies seem to exclude adverse effects of BPA [32], while others report adverse effects on child development and behavior [50][51][52].…”
Section: Bisphenol Amentioning
confidence: 99%
“…Findings have demonstrated connections between EED exposure and depression [12,13,14,15,16,17]. Based on discoveries that demonstrate that the Inhibitor of DNA-Binding/Differentiation (ID) proteins have been connected with depression [18,19,20,21,22], we will also emphasize how environmental EED exposure may modulate the depression outcomes via ID proteins. The goal of this review is to make links between ID proteins to EED interactions, thus, leading to altered results in depression.…”
Section: Introductionmentioning
confidence: 99%